If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4d + -6 = 10 Reorder the terms: -6 + -4d = 10 Solving -6 + -4d = 10 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -4d = 10 + 6 Combine like terms: -6 + 6 = 0 0 + -4d = 10 + 6 -4d = 10 + 6 Combine like terms: 10 + 6 = 16 -4d = 16 Divide each side by '-4'. d = -4 Simplifying d = -4
| n+5=5n | | 1/4u-7=-2/3u-7/4 | | 0+50-60-60*0+10=10 | | (7+x)(2)+(7-x)(2)=130 | | -10(4X+3)=-15X+19 | | 8x(x^2+4x-8)= | | 0.07x+9.95=9.1x-4.5x+12.47-4.6x | | 2.5+1.3= | | 24u^4w^5x^3-18u^6w^9= | | (10y/9x^5y^2)*(3x/2y | | 0.7n-15+n=1.2+1.5n-9.2 | | 129.46=2.15h+73.56 | | (x+2)(x+2)=(2x-1)(x-4) | | 5x+9=5x-35 | | 1/3x-2/5=-3/2 | | (9x^4-27x^6)/(3x^3) | | -1.4x=1.078 | | 9x(3+x)=3x-16 | | (8+v)(4v-7)= | | =3xa+3x | | -6+x=3x+8 | | 4-2m=5m-3 | | ((x-2)/4)-1=((x-9)/5) | | 20b^2-25b^3= | | ((x-2)/4)=((x-9)/5) | | 223x+27=476-3 | | -x-2x=-1 | | x+(3.5x)=90 | | 5(x)+x=1200 | | y(x)=3x^4-6x^2-1 | | 10=X+2.5 | | 4/3•3.14•9^3 |